Mathematisation: Channelising Children’s Enthusiasm for Developing Concepts in Mathematics - Fatima, Roohi (THE PRIMARY TEACHER, 2019)
Mathematics! With a slight change in spelling, it can be read as “Ma – the – Magic”. Ma – is the creator and creation is knowledge. All knowledge is the creation of mathematics. Humans, with the highest developed intellect, observe and perceive the physical and biological world around them. They process it in the mind and store it in the form of knowledge. One can notice that all ‘knowledge’ is in the form of NUMBERS? It is MAGIC. How old is civilisation? How many colours are there in the rainbow? What is the circumference (or radius) of the earth? How many stars, planets, satellites, continents, mountains, oceans, and rivers are there? How many people are there in a country? The answer to all these questions is in some form of ‘numbers’. There is no situation where numbers do not exist. The human mind works in numbers. The human body is represented through numbers. How many bones, hands, feet, fingers, eyes, and ears are there? Therefore, one has to consider ‘all knowledge’ as an offshoot of mathematics and mathematics as the mother of all ‘knowledge?’ Now the question is: ‘How to ‘Mathematise the knowledge’? How to make children realise that mathematics is nothing but the life they live.